Urine protein concentration estimation for biomarker discovery - Mistry, Hiten D.; Bramham, Kate; Weston, Andrew; Ward, Malcolm; Thompson, Andrew; Chappell, Lucy C. (Elsevier, 2013)
Recent advances have been made in the study of urinary proteomics as a diagnostic tool for renal disease and pre-eclampsia which requires accurate measurement of urinary protein. We compared different protein assays (Bicinchoninic acid (BCA), Lowry and Bradford) against the ‘gold standard’ amino-acid assay in urine from 43 women (8 non-pregnant, 34 pregnant, including 8 with pre-eclampsia. BCA assay was superior to both Lowry and Bradford assays (Bland Altman bias: 0.08) compared to amino-acid assay, which performed particularly poorly at higher protein concentrations. These data highlight the need to use amino-acid or BCA assays for unprocessed urine protein estimation.